2015
DOI: 10.3748/wjg.v21.i19.6001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of disease specific knowledge and health-related quality of life among United States military veterans with inflammatory bowel disease

Abstract: AIM:To evaluate the association between patient disease knowledge of inflammatory bowel disease (IBD) and health related quality of life (HRQoL) and identify patient and disease related predictors of patient knowledge of IBD. METHODS:We performed a cross-sectional study of IBD patients with an established diagnosis of IBD longer than 3 mo prior to enrollment. The Crohn's and colitis knowledge score (CCKNOW) and short inflammatory bowel disease questionnaire (SIBDQ) were selfadministered to assess patient kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
7
13
0
Order By: Relevance
“…The highest mean CCKNOW scores that have been published are 12Á4 in UC and 12Á6 in CD patients, and these scores occurred in patients who are members of an IBD association (Eaden et al 1999). Our results revealed that the patients with UC exhibited lower CCKNOW scores than the patients with CD, and similar results have been reported in other studies (Subasinghe et al 2010, Hou et al 2015, Yoo et al 2015. This difference might be explained by the fact that patients with CD have more hospitalisations and surgeries than patients with UC (Simian et al 2014, Niewiadomski et al 2015, and thus, they have more opportunities to share information with specialists.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The highest mean CCKNOW scores that have been published are 12Á4 in UC and 12Á6 in CD patients, and these scores occurred in patients who are members of an IBD association (Eaden et al 1999). Our results revealed that the patients with UC exhibited lower CCKNOW scores than the patients with CD, and similar results have been reported in other studies (Subasinghe et al 2010, Hou et al 2015, Yoo et al 2015. This difference might be explained by the fact that patients with CD have more hospitalisations and surgeries than patients with UC (Simian et al 2014, Niewiadomski et al 2015, and thus, they have more opportunities to share information with specialists.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the patients with the disease for less than one year exhibited lower disease-related knowledge than patients with longer histories of IBD. This result is similar to those of previous studies (Hou et al 2015, Yoo et al 2015 but differs from other studies that did not find any association between the disease duration and patient knowledge (Eaden et al 1999, Rezailashkajani et al 2006.…”
Section: Discussionsupporting
confidence: 87%
“…However, we found that CD patients obtained significantly higher scores than UC patients, particularly in the clinic, treatment, surgery and lifestyle domains. A similar trend was observed in this study using the CCKNOW and in previous studies using the KQ and CCKNOW questionnaires (14,25,26). A reasonable explanation for this bias is that CD patients are more likely to need surgical resection to treat disease complications in the regular clinical practice and are more often hospitalized than UC patients (2).…”
Section: Discussionsupporting
confidence: 89%
“…27 Patients diagnosed at younger age, having higher education qualifications (college/post graduate) had high CCKNOW score. This is a similar result from the study conducted by Jason K Hou et al 28 Patients in the young age groups had higher CCKNOW score as they require more information, regarding effective management of disease, than the other ones since they are active participants in social activities. Rather than high school graduates, university graduates showed more interest in disease management.…”
Section: Acknowledgementsupporting
confidence: 77%